Implementasi Good Governance dalam Pencegahan Budaya Koruptif: Studi Kasus PT Antam TBK - Aprinawati Aprinawati; Wulan Erdianti Putri; Windah Frawyta Lestary Sinaga; Yurida Aulia; Stephen Malau; Imamul Khaira (Journal on Education, 2024)
The purpose of this article is to analyze the role of good governance in preventing corruption in PT Antam, focusing on the application of the principles of transparency, accountability, and integrity in shaping an anti-corruption organizational culture. Using a qualitative approach with a case study method, this research identifies important elements of good governance, such as leadership with integrity, stakeholder participation, and an effective monitoring system. The results show that failures in the implementation of good governance principles contribute to the emergence of a corruptive culture, especially in PT Antam's Precious Metals Management and Refining. Weak transparency, accountability, and internal supervision allow abuse of authority to occur thoroughly. This study recommends improving the implementation of good governance and strengthening the supervisory system to prevent corruption in the future.